La durabilité de l’oudmourte en république d’Oudmourtie et dans la diaspora oudmourte : une réflexion comparative - Toulouze, Eva (Anthropologica, 2017)
The results of the last Russian census in the Udmurt Republic about the knowledge of the vernacular “mother tongue” show a significant decrease, albeit the existence of an administrative Udmurt unit is supposed to support the use and the knowledge of Udmurt. On the other hand, in the Udmurt diaspora of Northern Bashkortostan, language knowledge and practice is widespread. This article shall discuss and compare these two realities and attempts to pinpoint the main elements that warrant the remarkable sustainability of Bashkortostan’s Udmurt language experience, while reflecting whether the conditions that explain language maintenance may be implemented in Udmurtia.